Green synthesized montmorillonite/carrageenan/Fe3O4 nanocomposites for pH-responsive release of protocatechuic acid and its anticancer activity - Yen, Pin Yew (MDPI, 2020)
Discovery of a novel anticancer drug delivery agent is important to replace conventional cancer therapies which are often accompanied by undesired side effects. This study demonstrated the synthesis of superparamagnetic magnetite nanocomposites (Fe3 O4-NCs) using a green method. Montmorillonite (MMT) was used as matrix support, while Fe3 O4 nanoparticles (NPs) and carrageenan (CR) were used as filler and stabilizer, respectively. The combination of these materials resulted in a novel nanocomposite (MMT/CR/Fe3 O4-NCs). A series of characterization experiments was conducted. The purity of MMT/CR/Fe3 O4-NCs was confirmed by X-ray diffraction (XRD) analysis. High resolution transmission electron microscopy (HRTEM) analysis revealed the uniform and spherical shape of Fe3 O4 NPs with an average particle size of 9.3 ± 1.2 nm. Vibrating sample magnetometer (VSM) analysis showed an Ms value of 2.16 emu/g with negligible coercivity which confirmed the superparamagnetic properties. Protocatechuic acid (PCA) was loaded onto the MMT/CR/Fe3 O4-NCs and a drug release study showed that 15% and 92% of PCA was released at pH 7.4 and 4.8, respectively. Cytotoxicity assays showed that both MMT/CR/Fe3 O4-NCs and MMT/CR/Fe3 O4-PCA effectively killed HCT116 which is a colorectal cancer cell line. Dose-dependent inhibition was seen and the killing was enhanced two-fold by the PCA-loaded NCs (IC50 –0.734 mg/mL) compared to the unloaded NCs (IC50 –1.5 mg/mL). This study highlights the potential use of MMT/CR/Fe3 O4-NCs as a biologically active pH-responsive drug delivery agent. Further investigations are warranted to delineate the mechanism of cell entry and cancer cell killing as well as to improve the therapeutic potential of MMT/CR/Fe3 O4-NCs.